English Literature Students’ Performance in Writing Comparison and Contrast Paragraph Across Gender in Paragraph Writing Class - Nada Nisrina; Dian Safitri (Universitas Negeri Padang, 2023)
A growing body of research on writing skills has indicated male-female performance disparities. This study aimed to measure English Literature students’ performance in writing comparison and contrast paragraph and analyze differences across gender in paragraph writing class based on scores of writing and score of aspects of writing (content, organization, and language features). 38 students were chosen as participant with 16 male and 22 females. Descriptive quantitative research design was used with mid-evaluation paper as instrument and independent t-test and score analysis were done. Findings indicated English literature students’ performance was good in score of writing. In score of aspect of writing, they scored good (71-80) in content and organization but average (61-70) in language features. There was no significant difference between male-female literature students’ writing performance. In score of writing, male students scored average (61-70), while female students scored good (71-80). Both male-female scored good (71-80) in content. Male scored average (61-70) while female score good (71-80) in organization. Then, both male-female scored average (61-70) in language features.